Comparative evaluation of the shaping ability of two different nickel–titanium rotary files in curved root canals of extracted human molar teeth. Issue 1 (7th September 2015) - Ferrara, Giulia; Taschieri, Silvio; Corbella, Stefano; Ceci, Caterina; Del Fabbro, Massimo; Machtou, Pierre
Abstract: Aim: The aim of the present study was to compare the shaping ability of two different nickel–titanium rotary files in the curved root canals of extracted human molar teeth. Methods: Thirty root canals of 17 extracted human molars teeth were randomly assigned to two experimental groups ( n = 15): ProTaper Next and ProTaper Universal (PTU), on the basis of the rotary files system used. The final size of all apical foramina was 0.25 mm in diameter. Standardized digital radiographs were taken before and after instrumentation in both clinical and proximal views, with a size 10 K‐file inserted into the canal for the determination of the angle of curvature and apical transportation. Preparation time and fractured or deformed instruments were also recorded. The unpaired Student's t ‐test was used to compare results. Results: There was no significant difference between the two instruments with respect to canal straightening and apical transportation before and after instrumentation ( P > 0.05). The use of both instruments resulted in a significant reduction in the angle of curvature after instrumentation ( P < 0.05). Instrumentation time was significantly greater for PTU ( P < 0.05). Conclusions: The ProTaper Universal and ProTaper Next systems performed similarly with regard to the straightening of curved root canals and apical transportation. ProTaper Next was significantly faster than ProTaper Universal.